The Legitimacy of Letters as Evidence in the E-Litigation Proof System within the State Administrative Court - Bernadika, Shannon Rosemary; Afriyie, Frederick Appiah (Universitas Negeri Semarang (UNNES), 2023)
This study delves into the legitimacy of employing letters as evidence within the E-Litigation Proof System at the State Administrative Court (PTUN) against the backdrop of the digital 4.0 era’s transformative influence. The Indonesian government's introduction of electronic justice (e-Litigation or e-Courts) marks a significant paradigm shift, fundamentally altering trial procedures at PTUN. Employing a juridical-normative research method with a qualitative nature, this investigation utilizes conceptual and historical approaches to scrutinize the implications of the e-Litigation system. Secondary data sources, encompassing regulations, literature, and relevant documents, form the basis for analyzing the profound changes in courtroom proceedings and their impact on validating documentary evidence. The findings underscore a pivotal transition from traditional to electronic trials, fostering the electronic submission and exchange of documents. However, the implementation of the e-Litigation evidentiary system has sparked discussions, particularly concerning the legitimacy and challenges associated with proving letters as evidence, particularly in the initial stages of the process. This exploration of the legitimacy of letters as evidence within the e-Litigation context contributes significantly to the ongoing discourse on the modernization of legal proceedings. It sheds light on the evolving nature of evidentiary practices in the digital age, specifically within the State Administrative Court. The study thus offers valuable insights into the intersection of technology and justice, providing a nuanced understanding of the complexities surrounding the utilization of electronic evidence in contemporary legal systems.